Contra a correnteza: Rio Madre de Dios em Puerto Maldonado – Peru - Ricardo José Batista Nogueira; Thiago Oliveira Neto; Carlos Eduardo Silva Simões Rafael (Confins)
Rivers present fluvial dynamics of erosion and deposition that alter their banks, especially when these are located in areas of sedimentary formation as is the case of the Madre de Dios River in the Peruvian Amazon. For purposes of reducing the erosion process of one of the river banks and the collapse of the "carretera interoceánica sur", 12 enormous structures were built, which constitute metallic spikes called Defensa Ribereña La Pastora, which act as "wave breakers" slowing down the speed of the current, in an attempt to stop the process of erosion and undermining of the banks.